Perspectives of Endodontists and Pediatric Dentists on Regenerative Pulp Treatments - Rouhani, Armita; Gharechahi, Maryam; Hosseini, Zahra; Vatankhah, Pooya; Akbari, Majid; Babazadeh, Saber (Journal of Dental School, 2025)
Objective(s): This study aimed to evaluate and compare the perspectives of endodontists and pediatric dentists on pulp regeneration treatments, the frequency of their use, and their methods of implementation. Methods: The study employed a cross-sectional design. The sampling process involved distributing questionnaires to all mentioned specialists practicing in Mashhad in 2023. Chi-Square test was utilized to assess the association between categorical variables with the significance level set at 0.05. Results: A total of 67 specialists completed the questionnaires. 50.7% were endodontists, and 49.3% were pediatric dentists. 59.7% of the respondents stated that they had received training in regeneration treatments, 32.3% stated that they incorporate it into their practice. 66.2% of the specialists expressed willingness to participate in regeneration treatment training courses. Of the participants, 58.5% considered it to be successful, and 66.7% believed it to be a superior alternative to dental implants. 44.9% identified high cost as the main barrier to patient acceptance. 62.1% regarded pulp revitalization as the most valuable outcome, and 57.6% agreed that it is the optimal approach for necrotic immature teeth. Conclusion: Only 33% of specialists offered regenerative treatment, with over 50% of them utilizing it in less than 10% of their overall treatments. Endodontists were more inclined to provide this treatment compared to pediatric dentists. Most of the experts expressed interest in participating in a training course regarding regeneration.